The Ecranisation of the Wayang Padang Play Script by Wisran Hadi into a Film Script - Topan Dewa Gugat; Gangga Lawranta; Vereki Martiano; Vickrie Ardy (LPPM Institut Seni Indonesia Padangpanjang, 2025)
This research discusses the process of translating the drama script Wayang Padang by Wisran Hadi into a film scenario. Ecranization is the process of adapting from a text medium to a visual medium, which involves the transformation of narrative, characters and aesthetic elements. In this context, the research aims to identify the changes that occurred during the ecranization process, including story simplification, character adjustments, and visual processing to meet cinematic needs. The research results show that there are a number of significant modifications in the transfer from drama script to film scenario. Narrative transformation is carried out by simplifying the dialogue and storyline to create a more dynamic rhythm according to cinema needs. Visual development is a key element in the ecranization process, where the depiction of settings, costumes and character gestures are optimized to strengthen visual appeal. However, this research also found challenges in maintaining the cultural essence and moral messages contained in original works, especially in an effort to adapt them to modern audiences. The conclusion of this research emphasizes that the process of recreating the drama script